Language, Semantics, and Methods for Cryptographic Protocols - Crazzolara, Federico; Winskel, Glynn (BRICS Report Series, 2000)
In this report we present a process language for security protocols together with an operational semantics and an alternative semantics in terms of sets of events. The denotation of process is a set of events, and as each event specifies a set of pre- and postconditions, this denotation can be viewed as a Petri net. This Petri-net semantics has a strong relation to both Paulson’s inductive set of rules [Pau98] and strand spaces [THG98c]. By means of an example we illustrate how the Petri-net semantics can be used to prove properties such as secrecy and authentication.